Uses of wild edible plants in Quara district, northwest Ethiopia: implication for forest management - Mekuanent Tebkew; Yohannis Gebremariam; Tadesse Mucheye; Asmamaw Alemu; Amsalu Abich; Dagim Fikir (Agriculture & Food Security, 2018)
Abstract Background Wild edible plants are of crucial importance in all parts of the world in supporting global food basket (about one billion people) on a daily basis. They are means of survival for rural communities, especially during times of drought, famine, shocks and risks. This study assessed wild edible plants, uses, management practices and their threats in Quara district. It further investigates the implication of wild edible plants utilization for forest management. Methods Structured and semi-structured questionnaire interview, focus group discussion, rapid market survey and informants guided filed walks were used to collect data in three purposively selected administrative Kebeles. A total of ninety-four randomly selected sample households were interviewed for data collection. Both quantitative and qualitative data analyses were made. Descriptive and regression analysis were made to analyze the data using SPSS version 16.0. Results The area harbors a total of 36 wild edible plants. In addition to food values, these plants provide diverse benefits to the local community including income, fuel wood, fencing, construction, medicine and fodder. Adansonia digitata L., Ziziphus spina-christi Willd, Ximenia Americana L., Tamarindus indica L. and Balanites aegyptiaca L. were highly cited species by respondents. WEPs were threatened by anthropogenic factors including fire, agricultural expansion, deforestation, free grazing, fuel wood and construction. Conclusions Given the number of WEPs resource base, wise utilization and further commercialization of them could support local livelihoods while creating incentive for the management of forests. In addition, value addition could help to link the producers in and around the natural forests to the local, regional and international markets. Doing so will improve the incomes from the WEPs and creates further incentive for domestication. Controlling outsiders/nomads and designing participatory forest management will bring wise utilization of the resource.